Pengaruh Pengungkapan Corporate Social Responsibility Dan Penerapan Good Corporate Governance Terhadap Tingkat Profitabilitas (Studi Empiris Pada Perusahaan Sektor PertambanganYang Terdaftar Di BEI - Hari Setiyawati; Yusuf S. Basar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study aims to see the integration of accounting concepts in expressing corporate social responsibility and implementing good corporate governance, and achieving profitability level. This research is explanatory research intended to explain the causal relationship between variables through hypothesis testing. This analysis is used to determine the magnitude of the influence of independent variables on the dependent variable. This research is an empirical and grounded study conducted based on existing theories which then developed into a model of research where the model in this study is designed to examine the influence of corporate social responsibility disclosure and the implementation of good corporate governance to the level of profitability. This study aims to find and obtain empirical research evidence to obtain answers to research problems on how much influence the disclosure of corporate social responsibility and the implementation of good corporate governance to the level of profitability. The benefits of this research are to contribute scientifically to the science of financial accounting and management accounting and to solve problems for managers in the execution of tasks related to the increase in profitability level. The output of this research is in the form of publications in international journals.